The Impact of E-Wallet Usage on Student Shopping Behavior from the Perspective of Convenience and Impulsive Spending - Ananda Fristia; Dyah Ayu Megawaty (Eduvest - Journal of Universal Studies, 2026)
The rapid advancement of financial technology in Indonesia, particularly digital wallets (e-wallets), has significantly changed people’s transaction behavior, especially among university students. Easy access, fast payment processes, and attractive promotional features have made e-wallets a frequently used payment method in daily life. However, this convenience may also lead to increased impulse buying behavior, which involves purchasing goods or services spontaneously without prior planning. This study aims to analyze the impact of e-wallet usage on students’ impulse buying behavior, considering perceived ease of use and impulsive spending as mediating variables. A quantitative method was applied, involving 270 student respondents selected using purposive sampling. The research instrument was measured using a 5-point Likert scale and analyzed through descriptive statistics and Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS software. The findings show that e-wallet usage has a positive effect on perceived ease of use (β = 0.624), spending (β = 0.374), and impulse buying behavior (β = 0.183). Impulsive spending emerged as the most dominant factor (β = 0.844), while perceived ease of use showed a negative effect (β = −0.141). These results strengthen the Technology Acceptance Model (TAM) in the context of digital consumer behavior. Practically, the study highlights the importance of financial literacy and spending-control features to reduce excessive consumer behavior among students.